THE ROLE OF CUSTOMER SATISFACTION AND CUSTOMER VALUE IN MEDIATING THE INFLUENCE OF CUSTOMER EXPERIENCE ON CUSTOMER LOYALTY IN TRANSJAKARTA BUS SERVICES - Ahmad Ismail Hamdani; Moh Azib Mahfudhon (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
Transportation problems in big cities in Indonesia have become an acute problem, especially in public transportation modes, one of which can be seen from problems such as congestion and other public passenger transportation problems. Jakarta has made various efforts to provide public transportation that is comfortable, safe and able to reduce congestion in DKI Jakarta Province. This study aims to determine the role of customer value and customer satisfaction in mediating the effect of customer experience on customer loyalty. The sample used is Transjakarta Bus Users with 200 consumers as respondents. This research method uses a quantitative approach. The data analysis technique uses the help of the SEM (Structural Equation Modeling) application program which is operated through the AMOS software. The results of the study are 1. Customer Experience has a positive and significant effect on Customer Loyalty. 2. Customer Experience has a positive and significant effect on Customer Value. 3. Customer Experience has no significant positive effect on Customer Satisfaction. 4. Customer Value has a positive effect on Customer Loyalty. 5. Customer satisfaction has a positive and significant effect on customer loyalty. 6. Customer Value indirectly mediates the relationship between Customer Experience and Customer Loyalty. 7. Customer Satisfaction directly mediates the relationship between Customer Experience and Customer Loyalty.